Correlation Between the Width of Planting Line Toward the Growth of Red Meranti (Shorea leprosula Miq.) in Silvicultural System of Selective Cutting and Line Planting - Lilla Mutia; Prijanto Pamoengkas (Jurnal Silvikultur Tropika, 2014)
The demand of timber for industry is increasing, along with the increasing rate of population growth. It brings an impact toward the timber demand. Increased productivity is expected able to balancing the needs without caused a damage to the forest ecosystem it self. One of the silvicultural system which suitable to be implemented in natural forest is Selective Cutting Line Planting (TPTJ) which planted with S. leprosula species. One of the effort to increase productivity is by determining the land-width which suitable with the S. leprosula species, so that it can grows optimally. The result shows that there is a correlation between the width of planting line toward the growth of diameter and height. The optimum width for the S. leprosula planting line is 6 meters.